Pengaruh Pemanfaatan Teknologi Informasi, Pengetahuan Perpajakan, Dan Sanksi Pajak Terhadap Kepatuhan Wajib Pajak Orang Pribadi - Choirum Annisah; Susanti Susanti (Jurnal Pendidikan Akuntansi (JPAK), 2021)
The largest state revenue comes from taxes obtained from public contribution. If tax revenue tend to decline, then national development will be hampered. Because of this, the taxpayer compliance to pay taxes must be further improved. This study was held to analyze and determine the effect of model variables on individual taxpayer compliance. The approach used in this research is a quantitative approach by testing and analyzing the effect of the use of information technology, tax knowledge, and tax sanctions on individual taxpayer complianceat KPP Pratama Surabaya Wonocolo. Individual taxpayers who pay and report their tax at KPP Pratama Surabaya Wonocolo are used a population, with the sample is individual taxpayers whom the researcher meets accidentally and suitable as a data source. Based on the results of the t test, it is known that the information technology utilization variable has no and insignificant effect on individual taxpayer compliance, while the other independent variables, namely tax knowledge and tax sanctions have a positive and significant effect on individual taxpayer compliance. Likewise with the result of the f test which shows that the use of information technology, tax knowledge, and tax sanctions simultaneously has a positive and significant effect on individual taxpayer compliance.